Analysis of Online Learning Readiness Level at Universitas Nahdlatul Ulama Surabaya (UNUSA) - Endang Sulistiyani; Rizqi Putri Nourma Budiarti (International Journal of Innovation in Enterprise System, 2021)
Since a few years ago, blended learning has been implemented by UNUSA. However, until now, the implementation is still not optimal. Various obstacles, such as network access, availability of devices, and unclear rules in implementing online learning, still occur. Readiness analysis is one of the critical success in online learning implementation. The main objective of this research is to conduct online learning readiness studies at UNUSA. This research was carried out in three main stages: the preparation of measurement instruments, data collection, and analysis of readiness level. The method used is descriptive research method with quantitative and qualitative approaches. The Seakow & Samson e-learning readiness model with five dimensions of readiness, namely policy, technology, financial, human resource, and infrastructure, is used in this study. The result of this study shows that that UNUSA's level of readiness in implementing online learning is in the Ready category, requiring improvement to implement it with a readiness score of 3.68. The dimension with the highest score is technology, which is 3.84. Meanwhile, infrastructure and policy scored 3.77 and 3.72, respectively. The human resources dimension has a readiness score of 3.6. In contrast, the dimension with the lowest score is the financial dimension.